PHENOLIC ACID PROFILING IN THE LEAVES OF TABERNAEMONTANA HEYNEANA WALL. AN ENDEMIC PLANT OF THE WESTERN GHATS USING ULTRA-HIGH PERFORMANCE LIQUID CHROMATOGRAPHY COUPLED WITH QUADRUPOLE-TIME-OF-FLIGHT - MANASA DJ,; CHANDRASHEKAR KR, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The study was conducted to identify the phenolic compounds and other possible bioactive compounds present in the leaf extracts of Tabernaemontana heyneana Wall. Methods: Phenolic acid profiling was carried out using ultra-high-performance liquid chromatography coupled with quadrupole-time-of-flight (QTOF). An internal standard syringic acid was used for quantitation of phenolic acids and naringenin for quantitation of flavonoids. Results: The leaf extracts analysis revealed the presence of 17 compounds consisting of 14 phenolic compounds and three terpenes. Among 17 compounds, eight were the major compounds, namely, coniferyaldehyde, resveratrol, sinapic alcohol, protocatechuic acid, 4-hydroxybenzaldehyde, chlorogenic acid, rutin, and protocatechuic aldehyde. This forms the first report on the identification of these pharmaceutically important compounds in T. heyneana. Conclusion: These findings offer clear evidence and scientific support for further research on the leaf extract of T. heyneana plant for its therapeutic purpose.